The contractual processes of Colombian Public Private Partnerships: Fourth Generation of Road Concessions (2014-2018) (2019)
Public Private Partnerships (PPPs) have become a financial and technical solution mechanism for the construction, operation, maintenance, organization, exploration and exploitation of social and productive infrastructures that guarantee the provision of goods and services corresponding to the State. Although, the implementation of this type of concession in Colombia has generated an increase in the quality and coverage of the provision of some services, in the case of roads there has been poor road connectivity despite the contracted PPPs contracted. for the construction of the Fourth Generation of Road Concessions (4G), projects that seek Colombia to have productive and economic progress through a self-sufficient land structure. Therefore, this research aims to analyze the constitution of the contractual processes in the PPP of the Fourth Generation Road Concessions in Colombia between 2014 and 2018, through a detailed study of the current regulations on contracting and infrastructure, of the main failures evidenced in this type of contracting and, finally, there will be a recount of the main contracts failed by PPP of the 4G.